2020
DOI: 10.3390/ijerph17051766
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations, Possible Sources and Health Risk of Heavy Metals in Multi-Media Environment of the Songhua River, China

Abstract: Heavy metal pollution in the river environment has been a source of widespread interest due to potential threats to human health and ecosystem security. Many studies have looked at heavy metal pollution in the context of single source-pathway-receptor relationships, however few have sought to understand pollution from a more wholistic multi-media perspective. To investigate potential risks in a more wholistic way, concentrations of six heavy metals (Cd, Cr, Ni, Cu, Zn and Pb) were detected in multi-media (wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The concentration of Cr was significantly higher than that found in the Majiagou River ( p < .05) (Cui, Zhang, et al, 2019), which flows through the central area of Harbin City and has a relatively long history of receiving inputs/discharges of a large range of pollutants, while the concentrations of Cu and Ni were significantly lower ( p < .05). The concentrations of Cr and Ni were significantly lower than those in the Songhua River (Li et al, 2020) ( p < .01), while the concentrations of Cu and Zn were significantly higher ( p < .05). Considering that these three rivers are secondary tributaries of the Songhua River, the elevated levels of Cu and Zn may pose a negative effect on the water quality and the resident health because the Songhua River is an important source of drinking and irrigation water (Li et al, 2020).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The concentration of Cr was significantly higher than that found in the Majiagou River ( p < .05) (Cui, Zhang, et al, 2019), which flows through the central area of Harbin City and has a relatively long history of receiving inputs/discharges of a large range of pollutants, while the concentrations of Cu and Ni were significantly lower ( p < .05). The concentrations of Cr and Ni were significantly lower than those in the Songhua River (Li et al, 2020) ( p < .01), while the concentrations of Cu and Zn were significantly higher ( p < .05). Considering that these three rivers are secondary tributaries of the Songhua River, the elevated levels of Cu and Zn may pose a negative effect on the water quality and the resident health because the Songhua River is an important source of drinking and irrigation water (Li et al, 2020).…”
Section: Resultsmentioning
confidence: 80%
“…The concentrations of Cr and Ni were significantly lower than those in the Songhua River (Li et al, 2020) ( p < .01), while the concentrations of Cu and Zn were significantly higher ( p < .05). Considering that these three rivers are secondary tributaries of the Songhua River, the elevated levels of Cu and Zn may pose a negative effect on the water quality and the resident health because the Songhua River is an important source of drinking and irrigation water (Li et al, 2020). However, the concentrations of heavy metals were significantly lower than those in the Pearl River (except for Zn) ( p < .01), which is located in one of the most developed areas of China (Zhang, Bai, et al, 2017).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The health risk assessment for two population groups (adults and children) were done base on their body weight and exposure time. Increasing developmental and industrial activities along the river were identified as the cause of this pollution which was making the water unsuitable for use [18][19][20][21]. To the best of our knowledge, there has been no study conducted yet to investigate the water physicochemical parameters and heavy metal pollution from upstream to downstream of the river.…”
Section: Introductionmentioning
confidence: 99%
“…After continuous improvement by the U.S. EPA and other agencies, the four-step evaluation method has developed into a human health risk assessment model (HHRA) (US National Research Council, 1983), which has been widely accepted. It has been used to evaluate the human health risks of drinking water (Pérez et al, 2019;Kujlu et al, 2020), surface water (Zhang et al, 2015;Zhu et al, 2015;Li et al, 2020), groundwater (Edokpayi et al, 2018;, and polluted water by a large number of researchers. Zhao et al (2020) found that the human health risk through drinking water is two to three orders of magnitude greater than that of skin contact after the risk analysis of heavy metal pollution in the surface water of the Three Gorge Reservoir.…”
Section: Introductionmentioning
confidence: 99%